Flexible resource allocation during plant defense responses - Schultz, Jack C.; Appel, Heidi M.; Ferrieri, Abigail; Arnold, Thomas M. (Frontiers in Plant Science, 2013)
Plants are organisms composed of modules connected by xylem and phloem transport streams. Attack by both insects and pathogens elicits sometimes rapid defense responses in the attacked module. We have also known for some time that proteins are often reallocated away from pathogen-infected tissues, while the same infection sites may draw carbohydrates to them. This has been interpreted as a tug of war in which the plant withdraws critical resources to block microbial growth while the microbes attempt to acquire more resources. Sink-source regulated transport among modules of critical resources, particularly carbon and nitrogen, is also altered in response to attack. Insects and jasmonate can increase local sink strength, drawing carbohydrates that support defense production. Shortly after attack, carbohydrates may also be drawn to the root. The rate and direction of movement of photosynthate or signals in phloem in response to attack is subject to constraints that include branching, degree of connection among tissues, distance between sources and sinks, proximity, strength, and number of competing sinks, and phloem loading/unloading regulators. Movement of materials (e.g., amino acids, signals) to or from attack sites in xylem is less well understood but is partly driven by transpiration. The root is an influential sink and may regulate sink-source interactions and transport above and below ground as well as between the plant and the rhizosphere and nearby, connected plants. Research on resource translocation in response to pathogens or herbivores has focused on biochemical mechanisms; whole-plant research is needed to determine which, if any, of these plant behaviors actually influence plant fitness.